2017
DOI: 10.1002/nop2.86
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of women's experiences of living with COPD

Abstract: AimTo explore women's experiences of living with chronic obstructive pulmonary disease (COPD) at home.DesignAn explorative and descriptive qualitative design.MethodsA consecutive sample of nine women with COPD living at home. Data were collected in 2014 using semi‐structured interviews and analysed using a qualitative content analysis.ResultsThree main themes were identified: having a good life with COPD despite limitations; predictability and confidence in getting help; and the struggle to achieve a balance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…This disrupted their lives and their health behaviour. Such types of lived experiences were also reported by other studies among CRD patients, be it in the LMICs [15,17,30,[36][37][38] or in the developed world [39][40][41][42]. These experiences contributed to personal barriers to seeking treatment and adherence to treatment and hence overall physical and mental health outcomes [43,44].…”
Section: Interpretation In the Light Of Published Literaturesupporting
confidence: 64%
“…This disrupted their lives and their health behaviour. Such types of lived experiences were also reported by other studies among CRD patients, be it in the LMICs [15,17,30,[36][37][38] or in the developed world [39][40][41][42]. These experiences contributed to personal barriers to seeking treatment and adherence to treatment and hence overall physical and mental health outcomes [43,44].…”
Section: Interpretation In the Light Of Published Literaturesupporting
confidence: 64%
“…In the findings of Steindal et al (2017), some participants stated that they were unwilling to use a portable oxygen tank outdoors due to feeling embarrassed about their altered appearance. Disler et al (2016) indicate that the psychological impact of COPD led patients to live isolated lives.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown patients with COPD who lived alone to experience worse outcomes than their counterparts who lived with others (Crockett, Cranston, Moss, & Alpers, ; Gudmundsson et al, ). Previous studies have also briefly reported friends and neighbours to assist with instrumental daily living in patients with COPD who live alone but did not explore how they can assist in managing or preparing for breathlessness crises (Ek, Sahlberg‐Blom, Andershed, & Ternestedt, ; Steindal et al, ; Wilson et al, ). One other qualitative study in community‐dwelling older adults echoes similar themes to our study's findings: older adults were reported less likely to enter the acute care system if they were engaged in informal networks such as their peers and neighbours (Cheek, Ballantyne, & Roder‐Allen, ).…”
Section: Discussionmentioning
confidence: 99%